Social Determinants of Health: A Missing Link in Emergency Medicine Training. Issue 1 (18th September 2017) - Axelson, Daniel J.; Stull, Matthew J.; Coates, Wendy C.
Abstract: The health of a population depends upon several factors, including disease, public health initiatives, and the social determinants of health (SDH). These factors often converge in the emergency department (ED) where the impact of social conditions such as homelessness, low‐literacy, and poverty lead to recidivism and may contribute to provider burnout. Inclusion of SDH topics in EM residency curricula can provide needed background information and effective strategies for coping with these patients in the clinical setting. Exercises that simulate poverty, the development of and familiarity with meaningful community partnerships, and inclusion of SDH topics in standard ED conferences (e.g., mortality and morbidity conference) can promote understanding and outline a detailed plan for treating patients facing these challenges. By incorporating educational interventions aimed at identifying and intervening on issues of SDH in the ED we may be able to better serve those patients who need us the most.